The Everest story - Vicary, Tim. (New York : Oxford University Press, 2010)
"It is beautiful to look at, hard to reach, and terribly difficult to climb. Winds of 200 kilometers per hour or more scream across it day and night, while the temperature falls to -20 degree C or lower. Every year, some who try to climb the highest mountain in the world do not return. But for a century people have been coming to climb Everest - some alone, some in groups, but all with a dream of going to the highest place in the world. This is their story."--Page 4 of cover
English language and literature
Keywords: Mountaineering -- Everest, Mount (China and Nepal); High interest-low vocabulary books -- Livres de lecture facile; English language -- English language Textbooks for foreign speakers Environment; Everest, Mount (China and Nepal)